Investigating and Identifying Fish Illness in Aquaculture of Raised Fish: An Overview from the Proteomics Angle - Trapty Agarwal, Sonia Arora, Ganesh D (Revista Electronica de Veterinaria, 2024)
The growing demand for fish protein throughout the world is mostly met by aquaculture. However, the sector confronts issues including disease outbreaks that can have a major effect on fish health and productivity. Recognizing anomalous behavior, physical symptoms, and changes in appearance among grown fish are all part of diagnosing fish sickness in aquaculture. To preserve the health of the aquaculture system and to perform appropriate treatments, effective diagnosis is essential. The susceptibility of farmed fish to illnesses by improper husbandry techniques, outside variables like pollution and climatic change, and even modifications to the way products are traded within this industry, be one of the primary obstacles to aquaculture production. This study underscores the significance of using proteome analysis to uncover biomarkers, since this facilitates the creation of diagnostic instruments for the early identification of illness. Aquaculturists can lessen the effects of diseases on fish populations by taking targeted actions based on the identification of certain protein signatures linked to different fish illnesses.Proteomics is an example of a high-throughput technology that may be a valuable characterization implement, concentrated on the identification of pathogens and the virulence mechanisms connected to host pathogen interactions in the study and diagnosis of diseases that enforce the control, avoidance, in addition to treating illnesses in farmed fish. One important and promising method for studying fish illness is proteomics, which plays a significant role in knowing fish responses to environmental cues such stress and temperature, as well as pathogenic processes.